The Relationship between the Learning Environment and Student Learning Outcomes SDN 002 Gugus VI South Bontang Bontang City: Hubungan Lingkungan Belajar Dengan Hasil Belajar Siswa SDN 002 Gugus VI Bontang Selatan Kota Bontang - Nur Agus Salim; Afdal Afdal; Yoppi Indriani (Borneo Educational Journal (Borju), 2020)
This research aims to analyze the relationship between the learning environment and student learning outcomes at SDN 002 Gugus VI South Bontang, Bontang City. This research is quantitative research with a descriptive research type. Population is a generalization area consisting of Objects/subjects that have certain qualities and characteristics that researchers apply to study and then draw conclusions. (Sugiyono, 2016) The population in this study were all school residents at SDN 002 Gugus VI South Bontang, Bontang City, totaling 600 students. This research was carried out at SDN 002 Gugus VI South Bontang, Bontang City, East Kalimantan, Indonesia. The research period will start from April 2018. The results of this research show that the learning environment has a relationship with student learning outcomes at SDN 002 Gugus VI Bontang Selatan, Bontang City, meaning that if the student learning environment is good, it will encourage the learning outcomes obtained by students to be better, whereas if If the student learning environment is low, it will also encourage student learning achievement to be low.